Lament in the letter of James - Flynn, Grant (Biblical interpretation series, 2025)
"In Lament in the Letter of James, Grant Flynn presents the first book-length study of lament in James. After exploring the contours and development of Old Testament lament, Flynn examines the lament material in James, including a reference to an act of lament, allusions to Old Testament laments, and exhortations to lament. The author then proposes that the choice to use Job as a model of perseverance implies that Job's lament-shaped perseverance informs James's understanding of the virtue. By rereading the epistle's opening call to consider trials as "pure joy" with this Joban perseverance in mind, Flynn concludes that James envisions an ongoing cycle of lament and joy that reflects both the pain of human suffering and the hope of eschatological perfection"-- Provided by publisher